y = 3x-5
x^2 +(3x-5)^2 = 25
x^2 + 9x^2 -30x + 25 = 25
10x^2 -30x = 0
10x(x-3) = 0
so x = 0 or x = 3
When x = 0 y = -5
When x = 3 y = 4
2006-11-28 11:45:04
·
answer #1
·
answered by MollyMAM 6
·
0⤊
0⤋
Substitute y=3x-5 into other equation
x^2 + (3x-5)^2=25
x^2 + 9x^2-30x+25=25
10x^2-30x=0
10x=30
x=3
y=3(3/)-5 = 4
2006-11-28 11:53:59
·
answer #2
·
answered by af12af3af 2
·
0⤊
0⤋
the 1st poster is real up until this factor a million/4+y=a million y=a million+a million/4 <---- could be a million-a million/4 y=5/4 <---- could be 3/4 ----------------------------------- x + 3y = 2 -x + y = a million permit's use the 2d equation and remedy for y, because of the fact it quite is the greater straightforward of the two y=x+a million. replace into the firston x+3(x+a million) = 2 x +3x+3 = 2 4x = -a million x = -a million/4 making use of the fact that y = x+a million y=-a million/4 + a million y=3/4 continually a solid theory to envision and notice that each little thing works out. -a million/4 + 3(3/4) = 2 -a million/4 + 9/4 =2 8/4 = 2 2 = 2 -(-a million/4) + 3/4 = a million a million/4 + 3/4 = a million 4/4 = a million a million =a million yep
2016-12-13 16:20:46
·
answer #3
·
answered by shearin 4
·
0⤊
0⤋
y - 3x = -5
y = 3x - 5
x^2 + (3x - 5)^2 = 25
x^2 + ((3x - 5)(3x - 5)) = 25
x^2 + (9x^2 - 15x - 15x + 25) = 25
x^2 + 9x^2 - 30x + 25 = 25
10x^2 - 30x = 0
10x(x - 3) = 0
x = 0 or 3
y = -5
y = 4
ANS : (0,-5) and (3,4)
2006-11-28 13:05:24
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
y=3x-5
2x+2(3x-5)=25
2x+6x-10=25
8x-10=25
8x=35
x=35/8 approx 4.375
y-3(35/8)=-5
y-13.125=-5
y=8.125
2006-11-28 11:46:03
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋